Simulating the giant magnetocaloric effect-from mean-field theory to microscopic models - Amaral, J. S.; Amaral, V. S. (Frontiers in Materials, 2023)
Magnetocaloric materials are recognized as one of the major classes of magnetic materials for energy applications, and can be either employed as refrigerants in heat-pumping devices, or in thermomagnetic generators for energy conversion/harvesting. For both applications, having a material that presents a first-order magnetic phase transition is advantageous, as this typically leads to enhanced values of magnetization change in temperature (relevant to energy conversion) and of the magnetocaloric effect (relevant to heat-pumping). We present a brief overview of selected models applied to the simulation of applied magnetic field and temperature-dependent magnetization and magnetic entropy change of first-order magnetic phase transition systems, covering mean-field models such as the Landau theory of phase transitions and the Bean-Rodbell model, up to more recent developments using a Ising-like microscopic model with magnetovolume coupling effects. We highlight the fundamental and practical limitations of employing these models and compare predicted thermodynamic properties.